2007
DOI: 10.1177/0042085907304277
|View full text |Cite
|
Sign up to set email alerts
|

Does Homework Matter? An Investigation of Teacher Perceptions About Homework Practices for Children From Nondominant Backgrounds

Abstract: It is common for teachers in all districts across the United States to give homework to their students. Given the rising numbers of children from nondominant backgrounds1 in American schools, a question that merits consideration is how children from nondominant backgrounds—particularly in large urban centers—are impacted by teachers' homework practices. In this study we explored why teachers in one large U.S. urban center assign homework, the kinds of homework teachers assign, and teachers' beliefs about the i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
26
0
3

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(31 citation statements)
references
References 11 publications
2
26
0
3
Order By: Relevance
“…From the perspective of the latter, the whole English cohort and the Swedish halfcohort for whom homework was philosophically unproblematic, construed the consolidation of routine skills as an important part of the learning process (Brock et al, 2007;Earle, 1992). That being said, the two groups differed in both the manifestation of this belief and, in the case of the Swedish teachers, their philosophical perspectives.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…From the perspective of the latter, the whole English cohort and the Swedish halfcohort for whom homework was philosophically unproblematic, construed the consolidation of routine skills as an important part of the learning process (Brock et al, 2007;Earle, 1992). That being said, the two groups differed in both the manifestation of this belief and, in the case of the Swedish teachers, their philosophical perspectives.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, "few studies have focused on the teacher's role in the homework process" (Epstein & Van Voorhis, 2001, p. 181) or given them the opportunity to reflect on what are frequently unquestioned routines (North & Pillay, 2002). Moreover, with a few exceptions, most research on teacher perspectives has been conducted in the United States, where around nine teachers in every 10, irrespective of grade taught, believe that homework benefits students' learning, facilitates the development of both study skills and time management (Johnson & Pontius, 1989;Markow et al, 2007;Muhlenbruck et al, 1999) and, from the perspective of mathematics, provides necessary consolidation of material (Brock et al, 2007). However, the extent to which the deployment of homework is culturally determined is not well understood (Mau, 1997), a problem exacerbated by the invocation of common sense warrants (Davis, 2014) and cyclical educational trends throughout the twentieth century (Austin, 1979;Gill & Schlossman, 1996).…”
Section: Introductionmentioning
confidence: 99%
“…Homework assignment is not significant only in Turkish education system but also in the education system of other countries. Brock, Lapp, Flood, Fisher and Han (2007) stated that the homework assignment is one of the most common educational activities in the USA. They administed a survey questionnaire to 133 primary school teachers to analyse the goals of homework, homework types and the beliefs of teachers on the effects of homework on student achievement.…”
Section: Conclusion and Suggestionsmentioning
confidence: 99%
“…Homework research have reported teachers’ perspectives on their homework practices (e.g., Brock et al, 2007; Danielson et al, 2011; Kaur, 2011; Bang, 2012; Kukliansky et al, 2014), however, literature lacks research on the quality of homework. This study adds to the literature by examining the perspectives of teachers from two school levels regarding quality homework.…”
Section: Discussion and Implications For Practice And Researchmentioning
confidence: 99%